Enhancement of Liver Targetability through Statistical Optimization and Surface Modification of Biodegradable Nanocapsules Loaded with Lamivudine - Srikar Grandhi; Moawia Al-Tabakha; Prameela Rani Avula (Advances in Pharmacological and Pharmaceutical Sciences)
The intention of the current work was to develop and optimize the formulation of biodegradable polymeric nanocapsules for lamivudine (LMV) in order to obtain desired physical characteristics so as to have improved liver targetability. Nanocapsules were prepared in this study as aqueous-core nanocapsules (ACNs) with poly(lactide-co-glycolide) using a modified multiple emulsion technique. LMV was taken as a model drug to investigate the potential of ACNs developed in this work in achieving the liver targetability. Three formulations factors were chosen and 33 factorial design was adopted. The selected formulation factors were optimized statistically so as to have the anticipated characteristics of the ACNs viz. maximum entrapment efficiency, minimum particle size, and less drug release rate constant. The optimized LMV-ACNs were found to have 71.54 ± 1.93% of entrapment efficiency and 288.36 ± 2.53 nm of particle size with zeta potential of −24.7 ± 1.2 mV and 0.095 ± 0.006 h−1 of release rate constant. This optimized formulation was subjected to surface modification by treating with sodium lauryl sulphate (SLS), which increased the zeta potential to a maximum of −41.6 ± 1.3 mV at a 6 mM concentration of SLS. The results of in vivo pharmacokinetics from blood and liver tissues indicated that hepatic bioavailability of LMV was increased from 13.78 ± 3.48 μg/mL ∗ h for LMV solution to 32.94 ± 5.12 μg/mL ∗ h for the optimized LMV-ACNs and to 54.91 ± 6.68 μg/mL ∗ h for the surface-modified LMV-ACNs.